2023
DOI: 10.1111/srt.13463
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in exosomal non‐coding RNA‐based therapeutic approaches for photoaging

Kun‐Jie Li,
Peng‐Jun Zhou,
Yan‐Ni Guo
et al.

Abstract: BackgroundPhotoaging is a degenerative biological process that affects the quality of life. It is caused by environmental factors including ultraviolet radiation (UVR), deep skin burns, smoking, active oxygen, chemical substances, and trauma. Among them, UVR plays a vital role in the aging process.AimWith the continuous development of modern medicine, clinical researchers have investigated novel approaches to treat aging. In particular, mesenchymal stem cells (MSCs), non‐coding RNAs are involved in various phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 107 publications
1
3
0
Order By: Relevance
“…We observed that 70%–80% of total sEV proteins were identical among independent batches, higher than the reported 46.7% rate 12 . Functional analyses of biocargos confirmed the promising regenerative and anti‐inflammatory properties of ASC‐sEVs as already established 2,36 …”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We observed that 70%–80% of total sEV proteins were identical among independent batches, higher than the reported 46.7% rate 12 . Functional analyses of biocargos confirmed the promising regenerative and anti‐inflammatory properties of ASC‐sEVs as already established 2,36 …”
Section: Discussionsupporting
confidence: 70%
“…Notably, although ASC‐sEV treatment could increase level of anti‐oxidant enzymes in response to UVB, 42 we found that the treatment with loaded ASC‐sEVs upregulated these enzymes the most, explaining the lowest ROS level compared to sEV‐ and compound‐only treatments. Furthermore, our transcriptomic data did not detect changes in matrix metalloproteinases and collagen‐family genes as several reports about anti‐photoaging effect of sEVs 2,42,43 . This discrepancy was likely attributed to the different sampling time point as we collected RNA samples only 15 min after UVB irradiation to match with the ROS measurement, while others harvested 24–72 h later to investigate transcriptomic changes as consequences of ROS and maybe DNA damage 42,43 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The study of Li et al highlights the significant clinical promise of stem cells and their derivatives, including exosomes and noncoding RNAs, in rejuvenating aging skin and mitigating the effects of photoaging. 53 Applying exosomes directly after skin rejuvenation treatments like fractional laser, microneedling, radiofrequency micro-needling, and microdermabrasion aids in the healing process. This approach helps to mitigate symptoms associated with these procedures, including erythema, edema, and discomfort.…”
Section: Exosomementioning
confidence: 99%